Green Creativity and Voluntary Green Behavior: The Effect of Green Knowledge Sharing and Green Psychological Climate - Tehupuring, Ronald; Suhadarliyah, Suhadarliyah (Research Horizon, 2026)
The local government has mobilized village administrations to manage waste within their respective areas due to the escalating and poorly controlled waste problem in Ambon City.  This study aims the influence of green creativity on voluntary green behavior with green knowledge sharing as a mediator and green psychological climate as a moderator. This study employed a quantitative approach using purposive sampling to select 154 village officials from four sub-districts in Ambon City. Data were analyzed quantitatively using SEM-PLS to test the hypotheses and SPSS to assess correlations and common method bias. The results of this study found that green creativity has a positive and significant effect on voluntary green behavior, green creativity has a positive and significant effect on green knowledge sharing, green knowledge sharing has a positive and significant effect on voluntary green behavior, and green knowledge sharing can mediate the effect of green creativity on voluntary green behavior. This study also found that green psychological climate can strengthen the effect of green creativity on voluntary green behavior. The study suggests that fostering sustainable environmental behavior requires simultaneously strengthening green creativity, knowledge sharing, and a supportive psychological climate for optimal outcomes.